Influence of the oxygen adsorbed on tin varistors doped with Co, Mn and Cr oxides - Bacelar, W. K.; Oliveira, M. M.; Souza, V. C.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2002)
The non-ohmic properties of the 98.90% SnO2+(1-x)%CoO+0.05% Cr2O3+0.05% Nb2O5+x% MnO2 varistor system (all of them in mol %), as well as the influence of the oxidizing and reducing atmosphere on this system were studied in this work. Experimental evidence indicates that the electrical properties of the varistor depend on the defects that occur at the grain boundary and on the adsorbed oxygen species such as O''(2), O'(2), O in this region. Thermal treatments at 900 degreesC in oxygen and nitrogen atmospheres indicated such a dependence with the values of the non-linearity coefficient (alpha) increasing under oxygen atmosphere, being reduced in nitrogen atmosphere and restored after a new treatment in oxygen atmosphere, presenting a reversibility in the process. EDS analysis accomplished by SEM showed the distribution of the oxides in the varistor matrix. (C) 2002 Kluwer Academic Publishers.